The Key Stratum Structure Morphology of Longwall Mechanized Top Coal Caving Mining in Extra-Thick Coal Seams: A Typical Case Study - Fulian He; Xiaobin Li; Wenrui He; Yongqiang Zhao; Zhuhe Xu; Quansheng Li (Advances in Civil Engineering)
Longwall mechanized top coal caving mining (LMTCCM) in extra-thick coal seams has its own characteristics. The law of mining pressure and overlying strata failure height in extra-thick coal seams are much larger than those of medium-thick and thick coal seams. The key stratum structure morphology also has an important influence on the law of overlying strata movement and stability of surrounding rock. Based on the engineering geological conditions, this paper used the method of theoretical analysis and numerical simulation to study the key stratum structure morphology of LMTCCM in extra-thick coal seams. The results show that under the condition of LMTCCM in extra-thick coal seams, the key stratum forms the structure of low cantilever beam and high hinged rock beam. With the increase of coal seam thickness, the breaking position of cantilever beam is closer to the coal wall. Through theoretical calculation, it is obtained that the breaking length of cantilever beam is 31.5 m and the breaking position of cantilever beam is 15.4 m away from coal wall. With the increase of cycle, key strata will undergo the evolution law from the generation of longitudinal cracks to the hinged structure and then to the cantilever beam structure. The breakage of key strata will cause the expansion of longitudinal cracks and the overall synchronous movement of overlying strata. With the increase of coal seam thickness, the distribution of longitudinal cracks will gradually transfer from the upper part of goaf to the deep part of coal body in space and increase in quantity. This research is of great significance for improving the stability of overlying strata and ensuring the safe and efficient mining of extra-thick coal seams.